EVOLUTION OF ENGLISH IN THE INTERNET AGE - Al-Kadi, Abdu M. Talib; Ahmed, Rashad Ali (Indonesian Journal of Applied Linguistics, 2018)
Although the Internet came into existence in the second half of the twentieth century, its influence on language began to escalate in 1990 onwards. It has drastically changed the way people communicate and use English both in writing and speaking. Consequently, the world has become increasingly interconnected through synchronous and asynchronous communicational scripts, such as SMS, online chat, Yahoo messengers, emails, blogs, and wikis, which have become retrievable as accessible corpora for analysis. These corpora can yield anecdotal evidence of historical language change. The arrival of Web 2.0 tools and applications, such as Facebook, Twitter, Skype, WhatsApp, and Viber, can likewise reveal changes that English has recently undergone. The Internet has given rise to what is arguably a new variety of English that differs from standard varieties. This article provides an account of the development of English from dialects spoken by a small number of people in the British Isles to an international and global language. It emphasizes the language shifts that have taken place more recently since the widespread use of the Internet. The pervasiveness of the Internet has led to new changes in form and usage described as Internet English.